This Penyertaan modal usaha untuk membantu peningkatan kesejahteraan hidup keluarga disabilitas - Mundzir, Ilham; Fisabilih, Umirna; Az-Zahrawaani, Meilavisa (Fisip UIN Sunan Gunung Djati Bandung, 2024)
This community service activity aims to help improve the welfare of families with disabilities in order to be able to improve their business. Poverty in families with disabilities has become a major problem in poverty eradication in Indonesia. A person with a disability and their family still often facing stigma and discrimination in society, which can complicate daily life and limit their employment opportunities. Thus, this community service is by providing business capital to disabled families in the Lebak area. The YPAR (Youth Participatory Action Research) method that we will use in community service programs with collaboration between lecturers and students. This community service activity has been able to encourage families with disabilities to improve the quality of life by providing access to work and as an effort to increase the independence of family members who have disabilities which can be done through the provision of business capital.